Fractional Hermite-Hadamard Inequalities - Wang, JinRong; Fečkan, Michal (Fractional Calculus in Applied Sciences and Engineering ;, 2018)
This book extends classical Hermite-Hadamard type inequalities to the fractional case via establishing fractional integral identities, and discusses Riemann-Liouville and Hadamard integrals, respectively, by various convex functions. Illustrating theoretical results via applications in special means of real numbers, it is an essential reference for applied mathematicians and engineers working with fractional calculus. ContentsIntroductionPreliminariesFractional integral identitiesHermite-Hadamard inequalities involving Riemann-Liouville fractional integralsHermite-Hadamard inequalities involving Hadamard fractional integrals